2014
DOI: 10.1021/jp510293k
|View full text |Cite
|
Sign up to set email alerts
|

Initial Excited-State Structural Dynamics of 6-Substituted Uracil Derivatives: Femtosecond Angle and Bond Lengthening Dynamics in Pyrimidine Nucleobase Photochemistry

Abstract: Substituents on the pyrimidine ring of nucleobases appear to play a major role in determining their initial excited-state structural dynamics and resulting photochemistry. To better understand the determinants of nucleobase initial excited-state structural dynamics, we have measured the absorption and resonance Raman excitation profiles of 6-deuterouracil (6-d-U) and 6-methyluracil (6-MeU). Simulation of the resonance Raman excitation profiles and absorption spectrum with a self-consistent, time-dependent form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 20 publications
(112 reference statements)
2
32
0
Order By: Relevance
“…The addition of lithium sulfate did not noticeably change the absorption or resonance Raman spectra of 5,6‐ d 2 ‐U. The UV resonance Raman spectra of solutions containing 1 m m 5,6‐ d 2 ‐U and 0.3 m lithium sulfate internal standard were obtained at excitation wavelengths of 250, 257, 266, and 275 nm with laser powers of 5–12 mW, as previously described . Spectral slit widths were 5–7 cm −1 , and the total accumulation time was 20–30 min for each spectrum.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The addition of lithium sulfate did not noticeably change the absorption or resonance Raman spectra of 5,6‐ d 2 ‐U. The UV resonance Raman spectra of solutions containing 1 m m 5,6‐ d 2 ‐U and 0.3 m lithium sulfate internal standard were obtained at excitation wavelengths of 250, 257, 266, and 275 nm with laser powers of 5–12 mW, as previously described . Spectral slit widths were 5–7 cm −1 , and the total accumulation time was 20–30 min for each spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Previous elucidation of the initial excited‐state structural dynamics of C5‐and C6‐methylated uracil derivatives have shown that methyl substitution increases the initial excited‐state structural dynamics along the C5−C6 bond‐lengthening coordinate . Similarly, methyl substitution at C6 shows lower initial excited‐state distortional forces along the C5−X and C6−X in‐plane bends than substitution at C5 . We herein examine the initial excited‐state structural dynamics of 5,6‐dideuterouracil (5,6‐ d 2 ‐U) (Scheme ) by using resonance Raman and absorption spectroscopy to further test this model of C5/C6 substituent‐dependent initial excited‐state structural dynamics.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, the intensities of the resonance Raman peaks are proportional to the slopes of the excited‐state potential energy surface along each vibrational coordinate. The power of resonance Raman spectroscopy to probe the initial excited‐state structural dynamics of the molecules has been exploited by Loppnow et al in studying thymine, uracil, and their derivatives . The initial excited‐state structural dynamics of uracil in the photochemically relevant excited state is mostly directed along C5H and C6H bending modes, whereas it is oriented along the CC stretching mode in thymine …”
Section: Introductionmentioning
confidence: 99%